Audience Development of an Art Organization in Terms of Relationship Marketing - Pavlovaitė, Ugnė; Griesienė, Ingrida (Information & Media, 2019)
The article conceptualizes the audience of art organization, introduces the main art organization audience’s groups and analyzes the concept of relationship marketing in the context of art organizations. Relationship marketing tools are identified as an important instrumentality in order to develop and maintain networks between interested parties (various audience groups). The art industry is perceived as a medium for the implementation of relationship marketing. The theoretical platform model that is developed by art industry organizations is revealed as a universal and widely applicable tool among the biennials of contemporary art. The analysis of academic discourse presents the key groups of relationship marketing as well as dimensions which allows to evaluate the success of maintained networks. Following the features of public sector institutions a noticeable aspect in building relationships is the pursuit of economical benefit. Despite the economical benefits, interested audience groups of art organization are seeking of social benefits. At this point, the main relationship marketing dimensions – trust, commitment, satisfaction – are considered as a valuable measurement of the created platform network that reveals quality. It is concluded that arts organizations use appropriate relationship marketing tools to identify, establish, and maintain long-term relationships with their audience, for which the arts organizations provide additional organizational resources related to communication. The article presents an empirical study of the marketing relations of the biennial from research conducted in 2019 about the development of the biennial of contemporary art as an art platform where relationship marketing, as well as the main art organization audience groups, were presented. Case studies of the biennials of the contemporary art biennales Kaunas Biennial and EVA International were carried out. A qualitative study was chosen in order to empirically test the functioning of the theoretical model of the biennial as an art platform in terms of relationship marketing. Research data were collected using a qualitative (structured-standardized interview) research method. Following the analysis of the scientific literature and the empirical research data, guidelines for the development of an art organizations in terms of audience development were created.
Keywords: art organizations; audience development; relationship marketing; public sector; long-term relationship